2015
DOI: 10.1177/1460408615606753
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound in pre-hospital trauma care

Abstract: Pre-hospital medicine is developing rapidly. Increasingly, specialist pre-hospital medical practitioners are working in this environment and paramedics are advancing their skill base. Tools traditionally associated with hospital care are now used pre-hospital to improve diagnosis and intervention. In this paper, we assess the developing role of ultrasound in improving trauma care in the pre-hospital arena. Focused ultrasound is used to facilitate early diagnosis of pneumothorax and intraperitoneal/pericardial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 67 publications
(75 reference statements)
0
8
0
Order By: Relevance
“…Imaging is essential when dealing with critically ill patients, and LUS 148 , 216 is a remarkably versatile 217 imaging technique which, thanks to portable US devices, can be effectively performed before reaching organized medical facilities or during transport. 140 , 218 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Imaging is essential when dealing with critically ill patients, and LUS 148 , 216 is a remarkably versatile 217 imaging technique which, thanks to portable US devices, can be effectively performed before reaching organized medical facilities or during transport. 140 , 218 …”
Section: Methodsmentioning
confidence: 99%
“…Imaging is essential when dealing with critically ill patients, and LUS 148,216 is a remarkably versatile 217 imaging technique which, thanks to portable US devices, can be effectively performed before reaching organized medical facilities or during transport. 140,218 In the pre-hospital emergency setting, LUS can provide immediate yes/no diagnostic answers, as well as in-depth diagnostic evaluations, enabling or facilitating patient decision-making and management, and optimizing the allocation of resources. 219,220 The most common applications of LUS on the field are thoracic injuries and respiratory failure.…”
Section: Statement 12 (Clinical Statement)mentioning
confidence: 99%
“…In these studies, researchers found similar sensitivity and specificity in diagnoses compared to diagnoses made in in-hospital emergency department settings. 5,10,11 Another interesting study, this time with physicians who scanned 302 patients in an out-of-hospital setting, reported improvements in diagnostic confidence and accuracy with the use of ultrasound. 5 Our participants concurred, expressing that an improved diagnosis (as a result of ultrasound) may lead to changes in their triage, treatment, and management strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Their pooled results also suffered with considerable heterogeneity [38][39][40][41][42]. Previously published reviews involving pre-hospital thoracic POCUS for pneumothorax are exclusively narrative in nature [43][44][45][46][47][48]. Authors cite a paucity in suitable evidence at the time of writing as the reason why they did not conduct quantitative analysis.…”
Section: Accuracymentioning
confidence: 99%